An Analytical Approach to Stock Issue Management - Chandrapushpam, T. (International Journal of Engineering and Technology, 2018)
This paper is focused on developing an analytical formula for solving the stores issue management problem under First In First Out (FIFO) and Last In First Out (LIFO) methods of Queuing theory. Since the stores issue process follows the Queuing model for issuing materials to various departments, to arrive the conclusion price for closing stock it is necessary to update the balance stock with new arrivals and latest issues. In order to calculate the issue price which is issued from different lot, holding different price is actually a very big problem. To overcome this difficulty and to compute the closing stock price in the issue register the formulae get used. Moreover this study emphasis on issue orders with respective prices from various lots. Â